Japanese in thirty hours : - Kiyooka, Eiichi (The Seiwa-kai Society, 1946)
Vocabulary, selected examples, grammatical analysis, conversational expressions. This section is concluded by a chapter on funtional Japanese grammar, which supplements the lessons with a summary of other essential points of grammar.